Pengaruh Pemasangan Papan Iklan dan Kualitas Produk di Pippo Coffee Roasters Kota Batam - Ferrysah Putra; Rezki Alhamdi; Syafruddin Rais; Tito Pratama (CV. ITTC INDONESIA, 2025)
The growth of the coffee shop industry in Indonesia has increased over time, with the increasing culture of drinking or enjoying coffee among Indonesian people, especially in the city of Batam. In facing very tight market competition, marketing techniques such as installing billboards and improving product quality are important to attract consumer buying interest. This study aims to analyze the influence of billboards and product quality on consumer buying interest, with the object of research on Pippo Coffee Roasters. The research method used is quantitative with data collection through questionnaires to consumers, then validity and reliability tests will be carried out, classical assumption tests such as normality tests, heteroscedasticity tests and multicollinearity tests, then continued with multiple linear regression analysis such as t tests and f tests, as well as determination coefficient tests. The results of the study state that all instruments in this study are declared valid and reliable, and fulfill the classical assumption test, and the regression results show that the billboard and product quality variables have a positive and significant effect on the purchasing interest variable, both partially and simultaneously, and a very strong regression value with an R square value of 0.987. Thus, this research shows results that can be used as evaluation material by Pippo Coffee Roasters.